Implementasi Augmented Reality sebagai Pengenalan Benda Bersejarah di Museum Purbakala Popa Eyato Gorontalo Menggunakan Metode Marker Based Tracking - Sukayasa, I Nengah; Nasrullah, Asmaul Husnah; Melangi, Sudirman (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Abstract ; Augmented Reality is a technology that combines 2 or 3--dimensional objects into images on markers and then projects 3D objects directly. AR is very useful as a tourist data media to attract the attention of tourists both domestic and foreign tourists.  It also shares different experiences and guidance in mastering each place or tourist attraction visited. In making this application, the unity3D is used by applying the Marker Based Tracking method. This marker method is to detect markers in Augmented Reality applications so that they can display 3D visualizations of historical objects in the Popa Eyato Gorontalo ancient museum. The utilization of Augmented Reality technology in this recognition system can provide an overview of historical objects in the Popa Eyato Gorontalo ancient museum to increase its attractiveness to the public to get to know historical objects in the Popa Eyato Gorontalo ancient museum. Keywords: augmented reality, android, marker-based tracking, Vuforia